Coronary CT Angiography in the Emergency Department: State of the Art and Future Perspectives - Antonio De Vita; Marcello Covino; Sara Pontecorvo; Giacomo Buonamassa; Angelo Giuseppe Marino; Riccardo Marano; Luigi Natale; Giovanna Liuzzo; Francesco Burzotta; Francesco Franceschi (Journal of Cardiovascular Development and Disease)
About 5% of annual access to emergency departments (EDs) and up to 25–30% of hospital admissions involve patients with symptoms suggestive of acute coronary syndrome (ACS). The process of evaluating and treating these patients is highly challenging for clinicians because failing to correctly identify an ACS can result in fatal or life-threatening consequences. However, about 50–60% of these patients who are admitted to the hospital because of chest pain are found to have no ACS. Coronary computed tomographic angiography (CCTA) has emerged as a proposed new frontline test for managing acute chest pain in the ED, particularly for patients with low-to-intermediate risk. This narrative review explores the potential of adopting an early CCTA-based approach in the ED, its significance in the era of high-sensitivity troponins, its application to high-risk patients and its prognostic value concerning atherosclerotic burden and high-risk plaque features. Additionally, we address clinical and technical issues related to CCTA use for triaging acute chest pain in the ED, as well as the role of functional testing. Finally, we aim to provide insight into future perspectives for the clinical application of CCTA in the ED.